Hubungan Karakteristik Demografi dengan Tingkat Pengetahuan dan Perilaku Masyarakat Dusun Wohan Tampingan Kabupaten Magelang Terhadap Covid19 - Febriana Astuti; Jarot Styapurnomo (Universitas Malahayati, 2023)
ABSTRACT It has been more than two years since the Covid-19 pandemic, and it is not sure when this pandemic will end. The community has to start adapting to these conditions by continuing to do physical activities safely, applying health protocols in a disciplined and optimal manner, and not giving up fighting the Covid-19 pandemic. To prevent Covid-19, the community’s knowledge and behavior are very influential.Therefore this quantitative research focuses on examining the relationship between knowledge, demographics, and people's behavior related to Covid-19. This quantitative analytic study uses purposive sampling to determine the study's participants and uses a cross-sectional approach. There were 160 participants in this study. Data analysis used univariate and bivariate, which were processed using the Chi-Square test to see the correlation. The data of this study were analyzed using univariate and bivariate analysis, which was processed using the Chi-Square test to see the correlation between demographic characteristics, knowledge, and behavior, as well as the Spearman correlation test to see the relationship between knowledge and behavior.The results of the univariate analysis showed that the highest level of knowledge was in the